The Idea of “Race” in the Work of Juan Ignacio Molina, the Dispute of the New World and the Emergence of the National Myth (Andamios, Revista de Investigación Social, 2015)
An approach to the concept of “race” in the work of the Chilean naturalist Juan Ignacio Molina is presented in this paper, though this work fits into the context of the dispute of the New World and the history of science in Chile. We show how the concept of race contributed to the patriotic epistemology by legitimizing the social classifications in the first half of the nineteenth century, where the Creole elite was placed in a socially privileged position by asserting the myth of “pure blood”.
Keywords: Juan Ignacio Molina; blood purity; race; nation